Reduction Process of Tetraplatin in the Presence of Deoxyguanosine Monophosphate (dGMP): A Computational DFT Study - Šebesta, Filip; Burda, Jaroslav V. (Chemistry : a European journal, 2016)
The reduction mechanism of [PtIV(dach)Cl4] (dach=diaminocyclohexyl) in the presence of dGMP was studied. The first step is substitution of a chloro ligand by dGMP, followed by nucleophilic attack of a phosphate or sugar oxygen atom to the C8‐position of guanine. Subsequent reduction forms the [PtII(dach)Cl2] complex. The whole process is completed by a hydrolysis. Two different pathways for the substitution reaction were examined: a direct associative and a Basolo–Pearson autocatalytic mechanism. All the explored structures were optimized at the B3LYP‐D3/6‐31G(d) level and by using the COSMO solvation model with Klamt's radii. Single‐point energetics was determined at the B3LYP‐GD3BJ/6‐311++G(2df,2pd)/PCM/scaled‐UAKS level. Activation barriers were used for an estimation of the rate constants and these were compared with experimental values. It was found that the rate‐determining step is the nucleophilic attack with a slightly faster performance in the 3′‐dGMP branch than in the case of 5′‐dGMP with activation barriers of 21.1 and 20.4 kcal mol−1 (experimental: 23.8 and 23.2 kcal mol−1). The reduction reaction is connected with an electron flow from guanine. The product of the reduction reaction is a chelate structure, which dissociates within the last reaction step, that is, a hydrolysis reaction. The whole redox process (substitution, reduction, and hydrolysis) is exergonic by 34 and 28 kcal mol−1 for 5′‐dGMP and 3′‐dGMP, respectively. Calculated reduction: The mechanism of [PtIV(dach)Cl4] (dach=diaminocyclohexyl) reduction by dGMP and its derivatives, which consists of three reaction steps (substitution, reduction, and hydrolysis), is investigated by using DFT calculations. Two different pathways for the substitution reaction (associative or autocatalytic), which is the rate‐ determining step, were compared.